A comparison study: caregiver functioning and family resilience among families of children with cystic fibrosis, asthma, and healthy controls. Issue 2 (3rd April 2021) - Schneider, Mallory; Simpson, Jessica; Zlomke, Kimberly
ABSTRACT: Caregivers of children with cystic fibrosis (CF) are at risk for psychosocial difficulties, which has been related to poorer child well-being and medical adherence. The present study utilized the National Survey of Children's Health (NSCH) to examine self-reported differences in caregiver functioning among a matched sample of caregivers of youth with CF, asthma, and healthy controls ( N = 114). CF caregivers reported poorer mental health and more parenting aggravation. Among CF caregivers, poorer caregiver mental health predicted less family resilience, which in turn, predicted more parenting aggravation. Findings have implications for prevention screening and brief interventions within pulmonary medicine.